Analisis Aksesibilitas Pada Website Garuda Indonesia Menggunakan Tools Taw - Fitrianti, Shafira Balqis (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to evaluate accessibility level of the Garuda Indonesia website and the urgency for the company’s website offering services to be used by all groups, including people with disabilities. This evaluation refers to the Web Content Accessibility Guidelines (WCAG) version 2.0. The automation tool used for this evaluation is called TAW. The evaluation results show several indications of problems that affect accessibility level of the Garuda Indonesia website. Overall, it is sufficient to meet the level of accessibility based on four principles tested with a total of 50% from the entire success criteria.